(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2005)
Meaning of ’urban centre’ terminology is adaptable with urban history. Political situation; includes government system, geographical condition, history of the past are three major keys to understand the meaning of ’urban centre’. In Jakarta, Semarang and Surabaya, urban centre created a gap with city periphery. The gap, since 1980s, becomes less and less because the existence of small to medium scale industry which is located surrounding the city centre. During 1980s, political situation encouraged the types of industry to grow in developing country, such as Indonesia, which are firstly located in developed country. Street development in Indonesia also reduces the gap. In the 21st century, there is unbalance quantity of street length in big city; such as Jakarta, Surabaya, Bandung, and Semarang, and number of vehicle. Hence, this condition creates a new gap between city centre and periphery. Abstract in Bahasa Indonesia : Pengertian ’pusat kota’ pada kota-kota di Jawa terus berubah sesuai dengan perkembangan jaman. Keadaan sosial politik, termasuk sistim pemerintahan, letak geografis, serta sejarah masa lalu sebuah kota sangat berpengaruh pada kawasan yang disebut sebagai ’pusat kota’. Setelah th. 1980 an dengan adanya perpindahan industri skala kecil dan menengah dari negara maju ke negara berkembang yang sebagian besar bertempat di pinggiran kota-kota besar di Jawa seperti Jakarta, Surabaya dan Semarang, maka kesenjangan jarak antara pusat dan pinggiran ini makin tipis. Majunya transportasi mengurangi kesenjangan antara pusat dan pinggiran kota tersebut. Karena panjang jalan yang tidak seimbang dengan jumlah kendaraan pada abad 21, di kota-kota besar seperti Jakarta, Surabaya, Bandung dan Semarang, maka timbullah lagi kesenjangan antara pusat dan pinggiran kota. Kata kunci: Pusat Kota, Sejarah perkembangan kota di Jawa.